Tinjauan Aksiologi Terhadap Pensyariatan Iddah Perspektif Psikologi Hukum Keluarga - Hasanah, Uswatun; Harahap, Abdul Aziz (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
Iddah in Syara’ for divorced women is not just a waiting period, but an important process that must be passed to achieve ultimate peace, both mentally and physically. This research aims to trace the complex stages that women go through during the Iddah period, using field research methods with a descriptive analysis approach. The results show that the Iddah period serves as a means of psychological tranquillization in line with the principles of shara'. This process can be successful if the woman is patient and stays away from proposals that are contrary to sharia, as explained in the texts of the Qur'an and Sunnah. Therefore, women are encouraged not to put on makeup and to observe a period of mourning, as a form of devotion and an effort to get closer to Allah SWT.